Suture Button Fixation in Latarjet Has Similar Load to Failure and Clinical Outcomes but Lower Bone Resorption Compared With Screw Fixation: A Systematic Review - Hali, Nayeem Z; Tahir, Muaaz; Jordan, Robert W; Laprus, Hubert; Woodmass, Jarret; D'Alessandro, Peter; Malik, Shahbaz S (Arthroscopy, 2024)
To compare the 2 Latarjet fixation techniques-screw fixation (SF) versus suture button (SB) -for clinical, biomechanical, and radiologic outcomes. A systematic review was conducted in accordance with Preferred Reporting Items for Systematic and Meta-Analyses guidelines using MEDLINE and Embase databases and was prospectively registered on PROSPERO. Only comparative clinical and biomechanical studies of Latarjet with SF and SB were included. Studies were appraised using the Methodical Index for Non-Randomised Studies (MINORS) tool. Eleven studies met eligible criteria: 7 clinical studies (SB, n = 279; SF, n = 845) and 4 biomechanical. In total, 80.9% (SB) and 84.2% (SF) of patients were male. Follow-up ranged from 6 to 63.6 months. The overall recurrent instability rate for SB ranged from 0 to 8.3% and for SF ranged from 0 to 2.75%. Only one study demonstrated a greater recurrent instability rate with SB (P = .02). Overall SB complication rates ranged from 0 to 12.5% and SF ranged from 0 to 27%. Two studies reported greater complications and reoperations with SF related to hardware. Summary forest plots from 4 studies showed no significant difference in Walch Duplay score (mean difference, range -5.00 to 1.20 [95% confidence interval CI -12.13 to 8.56], I inconsistency = 0%), Rowe score (mean difference, range -2.00 to 4.00 [95% CI -7.37 to 7.66], I inconsistency = 45%), and VAS for pain (mean difference, range -0.10 to 0.60 [95% CI -0.72 to 1.33], I inconsistency = 0%). There was no statistically significant difference between SB and SF in the postoperative range of motion. Radiologically, there was no significant difference in graft positioning and union at final follow-up, but graft resorption was greater in SF (range 25.2%-47.6%) compared with SB (range 10.1%-18.5%). Biomechanical studies showed no significant difference in maximum load to failure (SB, range 184-266 N vs SF, range 148-288 N). Clinically, SB fixation demonstrated similar functional outcome and range of motion when compared with SF, with the potential benefit of lower rates of graft resorption and hardware-related complications. Biomechanically there was no difference in maximum load to failure. Level III, systematic review of Level III and biomechanical studies.